(untitled) (Eduscotech, 2024)
This study aims to examine the application of concepts related to children with special needs (ABK) in Early Childhood Education (PAUD) in Karangrejo District. The study employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews, participant observation, and documentation involving PAUD educators. The results indicate that educators possess a basic understanding of inclusive education; however, its implementation remains suboptimal due to limited training opportunities, insufficient supporting facilities, and constrained instructional time. Furthermore, collaboration among educators, parents, and the community emerged as a crucial factor in supporting the successful implementation of inclusive education. This study recommends strengthening educator training and providing adequate facilities to achieve inclusive and accessible PAUD services for children with special needs